PENGARUH KUALITAS LINGKUNGAN PENGENDALIAN (CONTROL ENVIRONMENT) TERHADAP KEANDALAN STRUKTUR PENGENDALIAN INTERN - , SUGIYANTO; , Dr. Sony Warsono, MAFIS, Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Internal control structure is a means to ensure the implementation of a good governance in an organization. Control environment serves as the foundation for other internal control components. A previous study conducted by Sanyoto (2006) revealed that external factors, attention, and human resources significantly affect the reliability of the internal control system. This study measured the quality of the environmental factors in internal control structure and the effect of the controlling environment quality on the reliability of the internal control structure. Primary data were obtained from the structural officials, perceptions including the heads of sub-divisions, divisions, and bureaus in XY University by sending 75 questionnaires to respondents. 70 of them were completed and returned to the researcher. One sample t-test, a mean of 4.20 and multiple regression were applied to analyse the data. The statistical analysis showed that factors in establishing integrity and ethics, commitment factors on the competence, the conducive leadership, the effective role of APIP and the cooperation with related institutions were reliable. On the contrary, the factors of the organizational structure, authority and responsibility delegations, practices, and human resources management policy were quite reliable. Beside, the internal control structure was quite reliable. The multiple regression analysis showed that the quality of the control environment significantly affected the internal control structure reliability and partially affected the quality of the commitment factors on the competence (KOMITKOM). In addition, the conducive leadership (KEPKON) significantly affected the reliability of the internal control structure